Inovasi Pembelajaran Puisi Melalui Alih Wahana Puisi Pada Non-Fungible Token (NFT) Art Gallery untuk Generasi Alfa - Kharisma Putriana Wardani; Haryanto, Muhammad (Edu Berkah Khatulistiwa, 2024)
In learning the Indonesian language, especially literature, several studies have found that students tend to avoid learning poetry at school because of the monotonous and conventional delivery and teaching design every year. Whereas the creative process of students, especially the alpha generation, in learning Indonesian language and literature must be balanced with digital technology that has never been explored before in the world of education. Poetry learning must evolve by integrating technological advances, including AI, AR, and VR, which can transform traditional poetry into an interactive digital format in accordance with the concept of an independent curriculum. In this research, the author designs a conceptual idea of poetry learning innovation through poetry ecranisasion in the AI-based NFT Art Gallery that introduces an immersive and interactive learning experience. The conceptual idea is designed as an alternative to learning poetry in the digital era, especially for the alpha generation. From the results of this study, learning poetry through poetry ecranisasion integrated with NFT Art Gallery shows that there are four stages of syntax, namely: (a) preparation activities, (b) implementation activities, (c) core activities, (d) closing activities. NFT Art Gallery is used as a learning media to demonstrate the results of poetry ecranisation. The conclusion of this study is that poetry ecranisation learning at the NFT Art Gallery can be an alternative technology-based learning solution for the alpha generation. The limitation of this research is that it has not been tested for effectiveness so that it becomes a recommendation for future research.